Pengaruh Manajemen Berbasis Sekolah, Kepemimpinan Transformasional Kepala Sekolah dan Supervisi Akademik terhadap Kinerja Guru dalam Implementasi Kurikulum Merdeka - Irhamudin Irhamudin; Choirudin Choirudin; Hasyim Asy’ari; Dumiyati Dumiyati (Attractive : Innovative Education Journal, 2025)
This study aims to analyze the influence of school-based management, the principal's transformational leadership, and academic supervision on teacher performance in implementing the Independent Curriculum in high schools in Metro City. This study used a quantitative approach with a survey method. The study population was all high school teachers in Metro City, with the sample determined using proportional random sampling. Data collection was conducted using a questionnaire that had been tested for validity and reliability. Data analysis used multiple linear regression. The results showed that, both partially and simultaneously, school-based management, the principal's transformational leadership, and academic supervision had a positive and significant effect on teacher performance in implementing the Independent Curriculum. The principal's transformational leadership variable had the most dominant influence. This finding emphasizes the importance of strengthening school governance, visionary Leadership and effective supervision play a crucial role in improving teacher performance and supporting the successful implementation of the Independent Curriculum. Therefore, this study contributes important insights into how strategic school leadership and continuous supervision can strengthen instructional quality, enhance teacher professionalism, and promote more effective and meaningful learning practices in the context of educational transformation